A Clinical Evaluation of Age and Metabolic Factors Affecting the Estimated Glomerular Filtration Rate - Tasrif Ahmad; Yosepin Galuh Sekar Khinanti; Debora Natasya Yusup; Aulisa Siska Nabila; Dewi Nurjanah Jaya Saputri; Lutfi Kurniawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Chronic kidney disease (CKD) remains a major global health challenge, characterized by a progressive decline in the estimated glomerular filtration rate (eGFR). Advanced age, sub-optimal glycemic control, and lipid abnormalities are well-established risk factors for renal dysfunction. This study evaluated the clinical profiles of subjects and analyzed the association between various clinical indicators and eGFR. A cross-sectional design was employed involving 317 participants. Data on age, HbA1c (specifically for diabetic individuals, n = 207), lipid parameters (Total Cholesterol, Triglycerides, LDL, and HDL), and renal function markers (Urea and Creatinine) were recorded. Descriptive statistics (mean, range, and standard deviation) were calculated, and bivariate associations were evaluated using Pearson’s product-moment correlation test. The mean age of participants was 60.67±10.64 years, with a mean eGFR of 73.90±25.24 mL/min/1.73 m², reflecting a mild reduction in renal function. Bivariate analysis demonstrated significant negative correlations between eGFR and age (r = -0.443, p < 0.001), urea (r = -0.695, p < 0.001), creatinine (r = -0.605, p < 0.001), and triglycerides (r = -0.114, p = 0.042). In contrast, eGFR correlated positively with HDL (r = 0.114, p = 0.042) and HbA1c (r = 0.171, p = 0.014). No statistically significant associations were observed for total cholesterol or LDL. Deterioration of renal function in this cohort is strongly linked to aging and metabolic disturbances. The positive correlation with HbA1c suggests early-stage glomerular hyperfiltration in diabetic patients. These results highlight the critical need for early metabolic intervention and periodic renal assessment, particularly among elderly and diabetic populations.